(untitled) (Journal of Social Sciences Review, 2025)
In this study, findings of a comprehensive survey of accounting educators’ opinions and practices concerning to ethics in accounting curriculum are presented. A questionnaire was used to gather the opinions of accounting faculty regarding the inclusion of ethics education in the accounting curriculum. Descriptive analysis techniques were used to analyze the survey results as the same method was used by researchers while conducting similar studies. As state boards across the globe require continued professional education in accounting curriculum, this study also finds that accounting faculty considers ethics education necessary for the profession’s needs. Accounting faculty themselves are most suitable for teaching ethics education and prefer real-world application over conventional academic content. As far as the methodology used to teach ethics is concerned, educators support integration in different subjects as opposed to a stand-alone course and support the view that study is the most useful technique for ethics education.